Rational selection of the polymeric structure for interface engineering of perovskite solar cells - YAVUZ, İLHAN (My University, 2022)
Tedious trial-and-error procedures are commonly practiced for surface modification of the perovskite solar cell (PSC) active layers. A guideline to rationally choose the passivating functional groups of the polymeric structure that is eminently effective in passivating the charged defects and elongating the device lifetime is hence in urgent demand. Herein, three prototypical polymers, poly(vinyl acetate) (PVA), polyethylene glycol (PEG), and poly(9-vinylcarbazole) (PVK), are selected to investigate the structural effect of the polymeric modification agents on the PSCs. We found that PVA possesses the Lewis base functional group with the minimized steric hindrance and the strongest electron-donating ability, enabling the most effective defect passivation on the perovskite film surface and the most enhanced carrier diffusion capacity. It demonstrates a power conversion efficiency (PCE) of 23.20% and noticeably enhanced operational stability. Our work provides important insights toward the selection of polymeric modification agents for high-performance and long-term stable PSCs.
Keywords: Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarımda Enerji; Biyoyakıt Teknolojisi; Kimya; Fizikokimya; Temel Bilimler; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Farm Machinery; Energy in Agriculture; Biofuels Technology; Chemistry; Physical Chemistry; Natural Sciences; Engineering and Technology; KİMYA, FİZİKSEL; Temel Bilimler (SCI); ENERJİ VE YAKITLAR; Mühendislik; Mühendislik, Bilişim ve Teknoloji (ENG); MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; Malzeme Bilimi; CHEMISTRY, PHYSICAL; CHEMISTRY; Natural Sciences (SCI); ENERGY & FUELS; ENGINEERING; Engineering, Computing & Technology (ENG); MATERIALS SCIENCE, MULTIDISCIPLINARY; MATERIALS SCIENCE; Enerji Mühendisliği ve Güç Teknolojisi; Yüzeyler ve Arayüzler; Yenilenebilir Enerji, Sürdürülebilirlik ve Çevre; Metaller ve Alaşımlar; Malzeme Kimyası; Genel Mühendislik; Genel Enerji; Kimya (çeşitli); Genel Malzeme Bilimi; Mühendislik (çeşitli); Genel Kimya; Yakıt Teknolojisi; Fiziksel ve Teorik Kimya; Yüzeyler, Kaplamalar ve Filmler; Enerji (çeşitli); Fizik Bilimleri; Energy Engineering and Power Technology; Surfaces and Interfaces; Renewable Energy, Sustainability and the Environment; Metals and Alloys; Materials Chemistry; General Engineering; General Energy; Chemistry (miscellaneous); General Materials Science; Engineering (miscellaneous); General Chemistry; Fuel Technology; Physical and Theoretical Chemistry; Surfaces, Coatings and Films; Energy (miscellaneous); Physical Sciences